Limnophyes guarani sp. n., a new hygropetric Orthocladiinae from southern Brazil (Diptera: Chironomidae) - Pinho, Luiz Carlos; Andersen, Trond (Zootaxa, 2015)
A new species of Limnophyes Eaton collected in the Corvo Branco Mountains in Santa Catarina State is described and figured, based on male and female adults, larva and pupa. The species groups with L. griseata (Edwards) and L. bidumus Sæther as the adults have a pronounced humeral pit with lanceolate setae and an additional group of lanceolate setae just posterior to antepronotum. The adults are, however, distinctly smaller, have a lower AR and have more lanceolate setae in the group just posterior to antepronotum than the two other species. The pupa can easily be separated from the pupa of L. bidumus as the anal macroseta is longer than the anal lobe. The larva lives hygropetric on vertical rock surfaces. A key to male adults of Neotropical Limnophyes is given.